2018
DOI: 10.14245/ns.1836050.025
|View full text |Cite
|
Sign up to set email alerts
|

Choice of Rods in Surgical Treatment of Adolescent Idiopathic Scoliosis: What Are the Clinical Implications of Biomechanical Properties? – A Review of the Literature

Abstract: The surgical treatment of adolescent idiopathic scoliosis (AIS) involves 3-dimensional curve correction with multisegmental pedicle screws attached to contoured bilateral rods. The substantial corrective forces exert a high level of stress on the rods, and the ability of the rod to withstand these forces without undergoing permanent deformation relies on its biomechanical properties. These properties, in turn, are dependent on the material, diameter, and shape of the rod. The surgical treatment of AIS is chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 64 publications
1
35
0
Order By: Relevance
“…Patients with fixed sagittal malalignment are unable to stand erect without flexing their hips or knees due to the loss of segmental lumbar lordosis (LL) 5,26,27) . Disruption of normal sagittal alignment results in significant pain and disability, and associated with low health-related quality of life 13) .…”
Section: Introductionmentioning
confidence: 99%
“…Patients with fixed sagittal malalignment are unable to stand erect without flexing their hips or knees due to the loss of segmental lumbar lordosis (LL) 5,26,27) . Disruption of normal sagittal alignment results in significant pain and disability, and associated with low health-related quality of life 13) .…”
Section: Introductionmentioning
confidence: 99%
“…It is known to be important that biomechanical properties are dependent on the material of rod. CoCr rod has in recent years been introduced for major spinal deformity surgery, which is characterized by a very high mechanical stiffness 7,20) .…”
Section: Discussionmentioning
confidence: 99%
“…However, most existing studies have mainly focused on the natural history of thoracolumbar curvature, and few studies have investigated cervical curvature. [8][9][10] In addition, as NMDs themselves are rare, there is a tendency for reports to focus on cerebral palsy, which is a relatively common NMD. 11 Generally, it has been reported that deformity curve progression is more common in patients with NMDs than in adolescent idiopathic scoliosis (AIS) patients with similar patterns.…”
Section: Natural History and Risk Factors For Spinal Deformity Progrementioning
confidence: 99%
“…By understanding the natural history of spinal deformities, we might be able to predict the probability and pattern of curve progression, and on that basis develop a treatment plan (e.g., the decision between surgical or conservative treatment), obtain informed consent from patients, and educate patients appropriately. However, most existing studies have mainly focused on the natural history of thoracolumbar curvature, and few studies have investigated cervical curvature [ 8 - 10 ]. In addition, as NMDs themselves are rare, there is a tendency for reports to focus on cerebral palsy, which is a relatively common NMD [ 11 ].…”
Section: Natural History and Risk Factors For Spinal Deformity Progrementioning
confidence: 99%